The hereditary progressive muscular dystrophy type 2A (calpainopathy): a clinical case - D. A. Grishina; N. A. Suponeva; V. V. Shvedkov; A. V. Belopasova (Нервно-мышечные болезни)
Presents clinical case the hereditary progressive muscular dystrophy type 2A (calpainopathy). Shows diagnostic difficulties and feature of presents clinical observations. This case is significance, as in the domestic scientific literature presents few articles on clinical examples of this muscle pathology.